Analisis Bahasa Kekuasaan pada Biografi Perjalanan 50 Tahun Surya Paloh - Slamet Parsono (Lembaga Penelitian Universitas Langlangbuana, 2019)
Media ownership is often used as a tool to perpetuate power to achieve certain political goals. Especially when the tap of a press release business license (SIUPP) was opened as wide as possible since the beginning of the 1998 reforms. From a simple perspective, the freedom to obtain SIUPP brought a breath of fresh air for investors to glance at the lucrative media sector. Don't be surprised if the term media conglomerate then sticks out, that is, mastering the mass media business in all its forms. Furthermore, the tendency of the desire for media ownership is bulging and creating his own work. From the perspective of media politics it is easy to predict that the role of media conglomeration leads to a host of dominant effects that have never been seen before. The work usually manifests in almost all restrictions on press freedom in the name of the interests of the community - and actually serves the special interests of certain groups, groups, groups, ideologies, institutions or individuals. Naughty indeed, the work is getting wilder in the midst of media competition to hunt for ratings.